Suffering related to dignity among patients at a psychiatric hospital - Skorpen, Frode (Nursing ethics, 2014)
This article discusses dignity from a Q-methodological study among patients at a psychiatric hospital. The aim of this study is to gain a deeper understanding of the subjective experiences of patients in a psychiatric hospital with respect to dignity. A Q-sample of 51 statements was developed. A total of 15 participants ranked these statements from those they most agreed with to those they most disagreed with. Post-interviews were also conducted. Principal Component Factor Analysis and varimax rotation followed by hand rotation produced the clearest results. Four different viewpoints emerged: being met as equal human being, experience of dignity despite suffering, suffering due to inferior feelings and suffering and fighting for one’s own dignity. There seem to be variations in those with dignity-promoting experiences in Viewpoint 1 and to some extent in Viewpoint 2, to those with dignity-inhibiting experiences in Viewpoints 3 and 4.